"Rights of Things": A Posthumanist Approach to Law?. Issue 1 (1st March 2021) - Schweitzer, Doris
Abstract: We can identify a legal vanishing point within neo-materialist and posthumanist approaches—either explicitly, for example, when things are regarded as political actors or contractual partners; or implicitly, when authors hint at the anthropocentric limitations of the granting of rights to human beings. Conversely, "rights of things" appear as a posthumanist approach to law as they decentralize "the human." But do "rights of things" actually surmount the strict divide between humans ( persona ) and nonhumans ( res ) within law? By referring to three empirical cases—animal rights, rights of nature, and robot rights—I will argue that "rights of things" do not necessarily push against the anthropocentrism of law. Rather, we can identify a re-centralization of humans within a given milieu. Thus, the critical impact of the concept "rights of things" must be reconsidered; furthermore, we can draw some conclusions for the theoretical approaches of New Materialism and Posthumanism itself.